"Homo Nooeconomicus" as a Human Image for the Noospheric Epoch - Grigory Smirnov; Alena Odintsova (International Society of Philosophy and Cosmology, 2019)
The article is devoted to the conceptualization of the "new homo economicus" model through the ideas of noospheric human image and noospheric economy. The authors claim that the epoch of noosphere requires a thorough review of human qualities core. It is shown that the image of a "due" economic entity can be based on the model of "homo nooeconomicus", whose key features are determined by the specificities of his worldview, realized from the perspective of the noospheric economic consciousness. The authors show that this form of consciousness provides the reflection and construction of relations between economic agents in the processes of manufacture, distribution, exchange and consumption of goods and services from the standpoint of fairness and responsibility in order to ensure reasonable sustainable socio-natural and socio-cultural development. It is stated that the cultural centers of the nooeconomic consciousness ensure creative, fair and responsible activity of the "homo nooeconomicus" in the biosphere, sociosphere, technosphere and the sphere of culture.